How to speak dragonese - Cowell, Cressida (Cowell, Cressida. How to train your dragon, 2010)
Recounts the further escapades of Hiccup Horrendous Haddock the Third as he continues his Viking training during which he escapes from a boatload of Roman soldiers and searches for his kidnapped dragon.